Pembelajaran Mitigasi Gunungapi Untuk Santri TPA Al-Amin Jleglongan Kulon Margorejo Tempel Sleman - fatimah, fatimah (ReTII, 2022)
Al-Amin TPA is a children's study group in the hamlet of Jleglongan, Margorejo, Tempel, Sleman whose students are mostly elementary school students but there are also small ones, from 4 years to 13 years old. Geographically, the hamlet of Jleglongan is close to Mount Merapi, this is what underlies the topic of devotion regarding learning about Volcano mitigation. The method used is lectures to convey knowledge of volcanoes and volcanic eruption disaster mitigation steps and demonstrations, namely video playback. The results of the service were also analyzed using the pired test statistical test. By using 10 questions and 10 statements where the result is 0.5 sigma. From the results of the analysis and discussion of questions and answers, the children generally already know, but the details of knowledge and mitigation steps still need to be explained. Statistical tests also explain that service is acceptable.